Thyroid hormones in centenarians in coronary artery disease - Svetlana V. Topolyanskaya; Tatyana M. Kolontai; Tatyana A. Eliseeva; Olga I. Turna; Olga N. Vakulenko; Leonid I. Bubman; Margarita A. Romanova; Karine A. Lytkina; Georgii G. Melkonyan; Svetlana A. Ratchina; Leonid I. Dvoretsky (Клинический разбор в общей медицине, 2023)
Aim. To analyze the relationship of thyroid hormones with various clinical and laboratory parameters in centenarians with coronary artery disease (CAD) based on the determination of the blood concentration of thyroid-stimulating hormone (TSH), free triiodothyronine (T3) and free thyroxine (T4). Materials and methods. This work was a cross-sectional study conducted on the basis of the Hospital for War Veterans No. 3. The study enrolled 262 patients [195 (74.4%) women and 67 (25.6%) men] aged 90 to 101 years (mean age 92.9±2.5 years) hospitalized with a diagnosis of coronary artery disease. The concentration of thyroid-stimulating hormone (normal 0.27–4.2 μIU/ml), the level of free T4 (12–22 pmol/l) and free T3 (3.1–6.8 pmol/l) in the blood were determined. Results. The mean level of TSH was 3.1±3.1 μIU/ml (0.005–108), free T3 – 3.7±0.65 pmol/l (1.9–5.3), free T4 – 14.1±5.5 pmol/l (4.1–32). In 18.9% of patients, the level of TSH was elevated, in 3.9% it was reduced, in 77.2% of patients it was normal. In patients with increased TSH lower functional activity was noted, assessed using the Barthel index (66.9±23.0 compared to 75.0±16.4 points in patients with normal TSH; p=0.02) and the IADL scale (3.46±2.3 and 4.6±2.0 points, respectively; p=0.006). Direct correlations were registered between free T4 concentration and uric acid (r=0.28; p=0.05), cholesterol (r=0.35; p=0.01), triglycerides (r=0.37; p=0.08), hemoglobin (r=0.23; p=0.07) and Morse fall scale (r=0.34; p=0.05). Significant inverse correlations were established between the blood concentration of free T4 and absolute indicators of bone mineral density in the lumbar spine (r=-0.36; p=0.03), in the proximal left (r=-0.44; p=0.006) and right (r=-0.43; p=0.009) femur. Conclusion. The study results demonstrate the relationship between the concentration of thyroid hormones and various clinical and laboratory parameters in centenarians with coronary heart disease.